Feedback Stabilization of Controlled Dynamical Systems In Honor of Laurent Praly - Petit, Nicolas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is a tribute to Professor Laurent Praly and follows on from a workshop celebrating the occasion of his 60th birthday. It presents new and unified visions of the numerous problems that Laurent Praly has worked on in his prolific career: adaptive control, output feedback and observers, stability and stabilization. His main contributions are the central topic of this book. The book collects contributions written by prominent international experts in the control community, addressing a rich variety of topics: emerging ideas, advanced applications, and theoretical concepts. Organized in three sections, the first section covers the field of adaptive control, where Laurent Praly started his career. The second section focuses on stabilization and output feedback, which is also the topic of the second half of his career. Lastly, the third section presents the emerging research that will form Laurent Praly's scientific legacy.
Part I: Adaptive Control -- Global Transverse Exponential Stability -- Model Reduction for Nonlinear Systems -- Network Small-Gain Theorems with Applications in Quantized and Event-Triggered Nonlinear Control -- From Theory to Practice in Adaptive Control: A Review -- Part II: Stabilization and Output Feedback -- An ODE Observer for Lyapunov-Based Global Stabilization of a Bioreactor Nonlinear PDE -- On State and Input Constraints in Nonlinear Systems -- High-Gain Nonlinear Observers with Limited Gain Power -- Asymptotic Stabilization by Means of Event-Triggered Output Feedbacks -- Contraction Theory as a Tool for the Design of Hybrid Control Systems -- Part III: New Perspectives -- Linear Transformations and Stabilization of Nonlinear PDE Control Systems -- Models and State Tomography of Open Quantum Systems -- Recent Developments for Stochastic Hybrid Systems.
Keywords: Control engineering; System theory; Control theory; Multibody systems; Vibration; Mechanics, Applied; Mathematical optimization; Calculus of variations; Control and Systems Theory; Systems Theory, Control; Multibody Systems and Mechanical Vibrations; Calculus of Variations and Optimization